Diversity Matters: Perceived Inclusion and Discrimination by Brazilian Tech Professionals - Sousa, Theo; Azevedo, Júlia; Ribas, Jessica; Uchôa, Anderson; Rocha, Larissa; Pereira, Juliana Alves (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2025: Anais do XXXIX Simpósio Brasileiro de Engenharia de Software, 2025)
Diversity and inclusion are widely recognized as essential drivers of innovation in software engineering. However, systemic inequalities and implicit biases remain persistent challenges. This study aims to explore how tech professionals in Brazil perceive inclusion, discrimination, and unconscious bias in the workplace. We surveyed 220 tech professionals, focusing on experiences of bias, perceptions of fairness, and the influence of organizational setting. The findings reveal that 95.2% of women experienced sexism, compared to 70.3% of men; 77.1% of non-white professionals identify racism as a key issue, while 61.5% of disabled professionals report experiencing ableism. Hybrid work models were associated with the highest reports of sexism (80%), while employees at smaller companies reported more frequent instances of ableism than those at larger ones. Despite widespread acknowledgment of discrimination, only 23% of respondents explicitly recognized the presence of unconscious bias in themselves. While most see their teams as diverse, leadership inclusion lags, especially for disabled (25.9%) and neurodivergent (36.4%) professionals. These results reveal persistent equity gaps and call for DEI (Diversity, Equity, and Inclusion) strategies in Brazil’s tech sector.